Anti-PD1 antibodies in patients aged ≥ 75 years with metastatic melanoma: A retrospective multicentre study. Issue 3 (April 2020) - Ridolfi, Laura; De Rosa, Francesco; Petracci, Elisabetta; Tanda, Enrica Teresa; Marra, Elena; Pigozzo, Jacopo; Marconcini, Riccardo; Guida, Michele; Cappellini, Gian Carlo Antonini; Gallizzi, Giulia; Occelli, Marcella; Pala, Laura; et al.
Abstract: Background: Advanced age is associated with comorbidities and immune system impairment, which may influence the efficacy and tolerability of immune checkpoint inhibitors. There is evidence that anti-PD1 antibodies in advanced melanoma are equally effective in patients >65 years. However, data on patients >75 years are lacking as co-morbidities and logistics often exclude them from clinical trials. Methods: We retrospectively reviewed the clinical records of older patients with advanced melanoma undergoing any-line treatment with an anti-PD1 (nivolumab/pembrolizumab) to investigate its clinical effectiveness and toxicity in a real-life setting. Clinical response was assessed using RECIST criteria and toxicity was evaluated according to CTCAE 4.0. Progression-free survival (PFS) and overall survival (OS) were estimated with the Kaplan-Meier method and the Cox model was used to assess potential prognostic factors. Results: 174 patients were considered; 59.2% males, median age 79 years (range 75–93). The majority had a performance status of 0 and normal lactate dehydrogenase (LDH) levels (55.2% and 52.4%, respectively). 69.1% had multiple co-morbidities. 56.9% received nivolumab. 36.7% of cases showed an objective response and the disease control rate was 56.3%. Median OS was 17.2 months [95% CI: 8.87-not reached] and a better prognosis was observed for patients with normal LDH ( p < .001) and lower performance status ( p < .001). Treatment was well tolerated, only 11 patients experiencing severe (grade 3/4) toxicity. There were no treatment-related deaths. Adverse events were managed with corticosteroids and additional immunosuppressive agents were unnecessary. Conclusions: Anti-PD1 antibodies appear effective and well tolerated in older patients with advanced melanoma .